A Systematic Literature Review: Impact of Generative AI as Technology to Learning in Higher Education - Suprobo, Winanti; Sucipto Basuki; Nurasiah (Khazanah Informatika : Jurnal Ilmu Komputer dan Informatika, 2024)
The development of generative Artificial Intelligence (AI) technology cannot be avoided because developments have entered all domains of life, including the world of education. Universities are preparing themselves to implement generative AI to support learning to be more efficient and effective without having to fear the threats it poses. The method used in this paper is a systematic literature review by exploring existing research through predetermined keywords. Extraction and selection of previous research results that are relevant to the topic are carried out and irrelevant topics are removed from the discussion. The papers produced from previous studies used as sources for the systematic literature review were 28 selected study papers, with range from 2004 to 2023. The most papers published in 2023 being 23 papers. The authors of the papers used were 24 authors from academic background, while the rest from industry and general publics. Generative AI, especially ChatGPT usage capabilities of learning in higher education, can create sophisticated text as humans do, as a virtual tutor and answer questions quickly, edit videos, help with manufacturing design, and act as language generation, language translation, and summarization. The advantages of Generative AI as a choice that cannot be underestimated and avoided and can be a responsive friend with accurate judgment. In order not to harm students, there needs to be strict and clear regulations so that the use of generative AI does not harm students, lecturers, and universities. Generative AI also has negative impacts, including decreasing knowledge productivity, ethics, and law becoming challenges, cheating, and hampering skill development, producing biased information, and low levels of privacy. In the future, universities should prepare clear regulations and policies for data security and privacy so that data remains safe and generative use has a positive and beneficial impact on higher education.